(untitled) (Per Musi, 2012)
In his fundamental book, A Theory of Musical Semiotics, Eero Tarasti endeavors to analyze Liszt’s piano workVallée d’Obermann from the point of view of semiotics. In a process of clever musical archaeology, the author revealsthe many layers that color the score of the Hungarian composer. The present article intends to make a few observationsat the margin of this text, trying to detail and comment the analysis by one of the most important Semiotics theoristsin the world.